Bioequivalence study of generic atenolol tablets in healthy Thai volunteers - Rojanasthien N. (2014)
Two preparations of 50 mg and 100 mg atenolol tablets were evaluated for their bioequivalence in twelve healthy Thai subjects (Prenolol, Berlin Pharmaceutical Industry, as the test formulations vs Tenormin, Zeneca Limited, as the reference formulations). A single oral dose of each preparation was administered in a randomized two-way crossover design, starting from either 50 mg of Prenolol vs Tenormin, thereafter, either 100 mg of Prenolol vs Tenormin. The washout period between each treatment was one week. Atenolol plasma concentrations were determined by the HPLC technique with fluorometric detection. Pharmacokinetic parameters were analyzed by the noncompartmental pharmacokinetic method using TOPFIT. The means and parametric 90 per cent confidence intervals of the ratio [Prenolol/Tenormin] of AUC0-infinity and Cmax were 1.16 (1.05-1.27) and 1.23 (1.07-1.38) for 50 mg preparations and 1.10 (1.00-1.20) and 1.13 (0.95-1.31) for 100 mg preparations, respectively. These values were well within the acceptable bioequivalence ranges. The mean differences of Tmax [Prenolol-Tenormin] were less than 20 per cent for both 50 mg and 100 mg preparations. Hence, Prenolol and Tenormin were bioequivalent with respect to the rate and extent of absorption.